Trend and Cycles in U.S. Real GDP - Gebhard Flaig (Center for Economic Studies and ifo Institute (CESifo), 2001)
In this paper an Unobserved Components Model is employed to decompose U.S. real GDP into trend and cycle components. The main findings are that there exist three cycles with a period of about two, five and 13 years, respectively, and that the long-run development during the last 50 years can be represented by a segmented linear trend with a break in the drift rate in the early seventies. A further result is a remarkable decrease in the volatility of the cycle component and the recursive residuals over the last two decades.
Keywords: 330; trend; cycle; unobserved components models; output gap